In vitro antioxidant and antibacterial activities of biogenic synthesized zinc oxide nanoparticles using leaf extract of Mallotus philippinensis Mull. Arg - Arun Kumar Khajuria; Anuj Kandwal; R. K. Sharma; Rakesh Kumar Bachheti; Limenew Abate Worku; Archana Bachheti (Scientific Reports)
Abstract The preparation of metallic nanoparticles (NPs) using the green method is rapid, eco-friendly, and easily scaled up at room temperature and pressure. In the current study, zinc oxide nanoparticles (ZnO NPs) were prepared utilizing leaf extract from Mallotus philippinensis, employing two distinct precursors of zinc oxide: zinc acetate and zinc nitrate. The antioxidant and antibacterial properties of the synthesized nanoparticles were also evaluated. The synthesis of ZnO NPs was preliminary monitored by UV–visible analysis. The biosynthesized nanoparticles were further characterized using a variety of techniques, such as Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM), and ultraviolet-visible (UV-Vis) spectroscopy. XRD peaks showed that nanoparticles synthesized from both zinc precursors exhibit crystalline properties, having wurtzite hexagonal shapes. The TEM analysis indicates that the average crystallite size was determined to be 21 nm and 28 nm for zinc nitrate and zinc acetate as precursor. FTIR analysis confirmed the presence of polyphenolic compounds on the surface of the nanoparticles, which likely acted as reducing and capping agents during ZnO NP synthesis. The antioxidant activity of M. philippinensis-mediated ZnO NPs was assessed in vitro. ZnO NPs synthesized using zinc nitrate exhibited higher antioxidant potential (IC50 = 65.31 µg/ml) compared to those synthesized using zinc acetate (IC50 = 66.87 µg/ml). Furthermore, the ZnO NPs demonstrated significant antibacterial activity against both gram-positive and gram-negative bacteria, including Klebsiella pneumoniae (K. pneumoniae), Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), and Streptococcus pneumoniae (S. pneumoniae). The highest antibacterial activity was observed against S. pneumoniae, with a zone of inhibition of 14.97 ± 0.38 mm for ZnO NPs synthesized using zinc nitrate. These findings suggest that M. philippinensis leaf extract is an effective reducing and capping agent for the biosynthesis of ZnO NPs. The resulting nanoparticles exhibit potent antioxidant and antibacterial properties, highlighting their potential applications in biomedical and environmental fields.